Okoljske obremenitve in stanje okolja na obalnem območju - primer Koprskega primorja - Cigale, Dejan (Geographica Slovenica, 2000)
Koprsko primorje is an example of coastal region with different kinds of environment pollution and different problems, intensified in this area due to various reasons. In the first part of the article same fact on the environment condition are stated and in the second part the examples of the environment pollution, connected to the activities, which are of the bigger importance for Koprsko primorje (tourism, traffic, etc.) or which can not be neglected regarding their impact on the environment condition, are stated.
Keywords: pokrajinska ekologija; environmental protection; varstvo okolja; onesnaževanje okolja; turistična geografija; prometna geografija; ekološko ravnotežje; sonaravni razvoj; Slovenija; Slovenia; coast; obala; Koprsko primorje; Slovenian Riviera